Reconstruction of precipitation variability in Estonia since the eighteenth century, inferred from oak and spruce tree rings - Helama, Samuli; Sohar, Kristina; Läänelaid, Alar; Bijak, Szymon; Jaagus, Jaak (Springer, 2018)
There is plenty of evidence for intensification of the global hydrological cycle. In Europe, the northern areas are predicted to receive more precipitation in the future and observational evidence suggests a parallel trend over the past decades. As a consequence, it would be essential to place the recent trend in precipitation in the context of proxy-based estimates of reconstructed precipitation variability over the past centuries. Tree rings are frequently used as proxy data for palaeoclimate reconstructions. Here we use deciduous (Quercus robur) and coniferous (Picea abies) tree-ring width chronologies from western Estonia to deduce past early-summer (June) precipitation variability since 1771. Statistical model transforming our tree-ring data into estimates of precipitation sums explains 42% of the variance in instrumental variability. Comparisons with products of gridded reconstructions of soil moisture and summer precipitation illustrate robust correlations with soil moisture (Palmer Drought Severity Index), but lowered correlation with summer precipitation estimates prior to midnineteenth century, these instabilities possibly reflecting the general uncertainties inherent to early meteorological and proxy data. Reconstructed precipitation variability was negatively correlated to the teleconnection indices of the North Atlantic Oscillation and the Scandinavia pattern, on annual to decadal and longer scales. These relationships demonstrate the positive precipitation anomalies to result from increase in zonal inflow and cyclonic activity, the negative anomalies being linked with the high pressure conditions enhanced during the atmospheric blocking episodes. Recently, the instrumental data have demonstrated a remarkable increase in summer (June) precipitation in the study region. Our tree-ring based reconstruction reproduces this trend in the context of precipitation history since eighteenth century and quantifies the unprecedented abundance of June precipitation over the recent years.
Keywords: ilmastotutkimus; sadanta; palaeoclimatology; proxy data; regional curve standardization; cyclonic activity; North Atlantic oscillation; Scandinavian pattern; Eesti; Viro; dendrokronologia; dendroklimatologia; paleoklimatologia; North Atlantic; klimatologia; sademäärä